Patterns and Correlates of Offender Versatility and Specialization Across a 23-Year Span for At-Risk Young Men. Issue 1 (2nd January 2018) - Wiesner, Margit; Yoerger, Karen; Capaldi, Deborah M.
ABSTRACT: The authors examined patterns and correlates of offender specialization versus versatility, or more random offenses, among 206 at-risk men. Both official records and self-report data of offending from late childhood to ages 31–32 years old were used. Aggregate- and individual-level analyses indicated that the predominant offender pattern for this sample was versatility. Three correlates of offender versatility were examined (offense frequency, early onset, gang association). Aggregate-level findings consistently revealed offense frequency as a robust correlate of offender versatility, whereas individual-level findings differed among the three measures of offender versatility. The congruence of these findings with predictions from Patterson's (1982) coercion model is discussed.